Polynomial Deceleration Parameter Explaining Bianchi Type I Model - Koly, Jenia Fardousi; Hossain, Md Nirab; Seum, Rashedul Islam; Ali, Md Showkat (GANIT: Journal of Bangladesh Mathematical Society, 2023)
The focus of the current research investigates the dynamical behavior of the universe within the framework of a new Bianchi type-I anisotropic, homogeneous astrophysical models with a modified theory of f(R, T) gravity. The significant effect of the model is to find solutions to the field equations using Polynomial Deceleration Parameter (PDP) which is a powerful tool to analyze the cosmic expansion history. Through a combination of theoretical analysis and graphical representation, we explore the consequences of f(R, T) gravity on the universe’s evolution for r = 1 to 5 polynomial value of DP. Our study unveils intriguing features in the context of this modified gravity theory, shedding light on its impact on cosmic expansion, acceleration, and potential deviations from standard cosmological models. The graphical representations provide intuitive insights, enhancing our comprehension of the complex interplay between geometry and matter content in the universe. This research contributes to a deeper understanding of the universe’s behavior in alternative gravitational theories. GANIT J. Bangladesh Math. Soc. 43.1 (2023) 08- 25